The Effects of Rice Husk Liquid Smoke in Porphyromonas gingivalis-Induced Periodontitis - Budhy, Theresia Indah; Arundina, Ira; Surboyo, Meircurius Dwi Condro; Halimah, Anisa Nur (European Journal of Dentistry, 2021)
Objectives The purpose of this study was to analyze the effects of rice husk liquid smoke in Porphyromonas gingivalis-induced periodontitis in the inflammatory and proliferation marker such as nuclear factor kappa β (NF-kB), tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), transforming growth factor-β (TGF-β), fibroblast growth factor 2 (FGF2), collagen type 1 (COL-1) expression, and the number of macrophages, lymphocytes, and fibroblasts.Materials and Methods Rice husk liquid smoke is obtained by the pyrolysis process. Porphyromonas gingivalis-induced periodontitis in 20 μL phosphate-buffered saline containing 1 × 109 CFU was injected into the lower anterior gingival sulcus of Wistar rats. The periodontitis was then treated with 20 μL/20 g body weight of rice husk liquid smoke once a day for 2 and 7 days, respectively. After treatment, the bone and lower anterior gingival sulcus were analyzed with immunohistochemistry and hematoxylin–eosin staining.Results The treatment of periodontitis with rice husk liquid smoke showed a lower NF-kB, TNF-α, and IL-6 expression and a higher TGF-β, FGF2, and COL-1 expression than the control after treatment for 2 and 7 days (p < 0.05), respectively. The number of macrophages and fibroblasts was also higher when compared with the control group (p < 0.05), but the number of lymphocytes was lower than the control (p < 0.05).Conclusion Rice husk liquid smoke showed its effects on Porphyromonas gingivalis-induced periodontitis with a decrease in inflammatory markers and an increase in proliferation markers. The development of a rice husk liquid smoke periodontitis treatment is promising.
Keywords: Porphyromonas gingivalis; periodontitis; liquid smoke; rice husk